Peripartum cardiomyopathy management-multidisciplinary approach 2011-2013 at Care Institute of Medical Sciences - Devabhaktuni, Pratibha; Chennapragada, Sridevi; Manchala, Sushma; Menon, Rajeev; Patil, Neelkanth; Bhupatiraju, Somaraju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Peripartum cardiomyopathy (PPCM) is one of the rare causes of heart failure in pregnant women. It occurs in late pregnancy or up to 5 months post-partum. It is associated with high mortality and morbidity but with chances of full recovery. This paper discusses the treatment of peripartum cardiomyopathy, Peripartum cardiomyopathy management -multidisciplinary approach. 2011-2013 at CIMS. Methods: This is an observational study conducted at CARE institute of medical sciences, CIMS, during 2011-2013 years. Women fulfilling the criteria for the diagnosis of PPCM were included in the study. In this study we have analysed the obstetric intervention, the duration of ICU stay, hospital stay, maternal and perinatal outcomes. The cardiac drugs to manage each individual case suited to her condition have been mentioned. Results: Six cases were diagnosed to have PPCM in pregnancy when there was sudden onset of shortness of breath, cough, and palpitations. Four cases had history of PPCM in previous pregnancies and were managed in the current pregnancy. One rare case had features of cardiomyopathy seen in early gestational period, during the first trimester at eight weeks, when she was treated for ectopic gestation. Patients were managed by pregnancy cardiac team. There was no case of maternal mortality. Conclusions: PPCM is a rare condition. It requires a high index of suspicion and awareness among primary care givers for early diagnosis and prompt management. A pregnancy cardiac team approach benefits this subset of patients. Delayed time of presentation, LVEF and dilated ventricle are factors determining recovery.